PENGARUH STRUKTUR PASAR DAN DAYA SAING TERHADAP KINERJA UMKM KERAJINAN KERAMIK DI KOTA MALANG - Vivin Setia Irnia; Abdul Wahid Mahsuni; Junaidi Junaidi (Universitas Islam Malang, 2020)
ABSTRACTThe purpose of this study was to determine the effect of market structure and competitiveness on the performance of ceramic handicrafts MSME in Malang. The population in this study were all ceramic craft SMEs in Malang. Data obtained From 30 UMKM ceramic crafts in Malang city. This research uses multiple linear regression models. The results of this study indicate that market structure and competitiveness together (simultaneously) affect performance. Partially the market structure variable does not affect the performance of SMEs ceramic crafts in the city of Malang. While the competitiveness variable has a positive effect on the performance of MSME ceramic handicrafts in Malang. Therefore UMKM Malang ceramics need to form a competitive advantage to be able to maintain their business.Keywords: Market Structure, Competitiveness, performance